Preeclampsia risk in 24 to 26 weeks gestation nulliparous pregnant women with early diastolic notch or resistance index >0,58 in uterine arteries - Acho Mego, Segundo (2015)
Objectives: To determine the risk of preeclampsia in pregnant nulliparous women who presented early diastolic notch (EDN) or resistance index (RI) >0,58 during Doppler evaluation of the uterine arteries between the 24th and 26th weeks of pregnancy. Design: Cohort study. Setting: Cayetano Heredia National Hospital. Participants: Nulliparous pregnant women. Interventions: Between March 2002 and July 2003 126 pregnant nulliparous women with 24 and 26 weeks of gestation were studied by color Doppler velocimetry of the uterine arteries. We considered exposure when EDN or RI >0,58 were present. Covariables considered were maternal age, legal status, body mass index and placental location. Development of preeclampsia was considered as the final outcome. Main outcome measures: Presence of early diastolic notch or resistance index >0,58 by color Doppler velocimetry and relation with preeclampsia. Results: The risk of preeclampsia was 12 times bigger (RR = 12; 95% CI: 1,65–102,66) in pregnant nulliparous women who presented EDN compared with pregnant nulliparous women who did not present this finding. The risk of preeclampsia was 7 times bigger in pregnant nulliparous women who presented this a RI >0,58 compared with pregnant nulliparous women who did not present this finding (RR = 7; 95% CI: 0,88-55,25). Conclusions: The risk of preeclampsia was significantly increased in pregnant nulliparous women who presented early diastolic notch between the 24th and 26th weeks of gestation.